Talking about obesity with clients: preferred terms and communication styles of UK pre-registration dieticians, doctors and nurses - Swift, Judy A.; Choi, Edith; Puhl, Rebecca M.; Glazebrook, Cris (Elsevier, 2013)
Objective To describe trainee healthcare professionals’ preferred terms when talking about obesity, their beliefs about initiating discussions about weight, and their confidence about consulting with obese people.